KRAS mutation in papillary fibroelastoma: a true cardiac neoplasm?. (7th March 2017) - Wittersheim, Maike; Heydt, Carina; Hoffmann, Fabian; Büttner, Reinhard
Abstract: Primary cardiac tumours are rare and mostly benign lesions. Recent publications report that cardiac papillary fibroelastomas are the most common benign primary heart tumour, outnumbering myxomas. However, there is no consensus about their aetiology. We investigated the molecular profile of these tumours using next generation sequencing in a cohort of 16 cases. Eleven of 14 (79%) analysable tumours showed mutations of the KRAS oncogene. Our results provide unambiguous evidence that a significant proportion of these lesions are genuine neoplastic tumours caused by an oncogenic driver mutation.